Study of Antibiotic Resistance and the zapA Gene in Proteus Mirabilis Isolated from Patients with Urinary Tract Infections - Aevar Ashraf Khorshed (American Journal of Biomedicine and Pharmacy, 2025)
Background & aim: Proteus mirabilis are Gram negative bacteria belonging to the family of Enterobacteriaceae and have been implicated in a number of infections. In conclusion, the present study was conducted to investigate antibiotic resistance and zapA gene in P. mirabilis from patients with UTI. Materials & methods: A total of 130 urine samples obtained from patients at Azadi Teaching hospital between March and July 2025 were included in this study. Based on the culturing features of the P. mirabilis colonies developing on MacConkey agar media, the colonies were diagnosed and incubated for 24 hours at 37 0C. the DNA was extracted to detecting ZapA gene for each isolate. Results: According to the results, 32(24.6%) of the total samples showed positive results for the growth of P. mirabilis when it was cultured on MacConkey agar. Biochemical tests for P. mirabilis bacteria appear to be negative for Indole, oxidase, while, P. mirabilis were positive for urease, citrate, motility, catalase and Kligler iron k/A H2S. For antibiotic test, P. mirabilis showed a low sensitive 34.4% toward Ceftazidime and a complete resistant 100% toward Ampicillin. Otherwise, P. mirabilis showed high sensitive toward 81.3% Imipenem, 81.3% Levofloxacin, 87.5% Gentamicin, and 90.6% Amikacin respectively. After isolating DNA from P. mirabilis using an extraction and electrophoresis kit, it was found that 100% of P. mirabilis isolates contained the zapA gene. zapA virulence gene was detected in all 32 Proteus mirabilis isolates (100%). Of these, 1 isolate (3.1%) was XDR, 21 isolates (65.6%) were MDR and 10 isolates (31.3%) were sensitive /non-MDR/XDR with there being no significant relationship between the presence of zapA and resistance patterns (p >0.05), suggesting that virulence is not linked to antibiotic resistance. Conclusions: The results indicate that P. mirabilis is an important cause of urinary tract infections and is characterized by a wide range of resistance to antibiotics. On the other hand, it was found that P. mirabilis was very sensitive to Amikacin, and the ZapA gene was found in all isolates, which explains the virulence of the bacteria.